Residual biomass of coffee as a binding agent in diffusive gradients in thin-films technique for Cd, Cu, Ni, Pb and Zn measurement in waters - Yabuki, Lauren N.M. [UNESP]; Menegário, Amauri A. [UNESP]; Gemeiner, Hendryk [UNESP]; Rolisola, Ana Marta C.M. [UNESP]; Gastmans, Didier [UNESP]; Williams, Paul N. (Elsevier, 2019)
Spent coffee grounds (SCG) immobilized in agarose gel are proposed as a novel binding agent for application in the Diffusive Gradients in Thin films (DGT) technique for the determination of Cd, Cu, Ni, Pb and Zn in waters. The SCG-agarose gel was characterized by Scanning Electron Microscopy, Energy Dispersive X-ray Spectrometry and Porosimetry by nitrogen adsorption. Elution of analytes from the binding agent was effectively performed with 2 mol L−1 HCl. The effects of key DGT parameters (e.g. immersion time, ionic strength and pH) were evaluated with a deployment of DGT devices (DGT-SCG) in synthetic solutions with ionic strengths between 0.005 mol L−1 and 0.1 mol L−1 and within a pH range of 3.5–8.0. The results were in excellent agreement with the predicted theoretical curve for mass uptake. Consistent results were found for solutions with ionic strengths between 0.005 mol L−1 and 0.1 mol L−1 and within a pH range of 3.5–8.0. The DGT-SCG performance was also evaluated in two spiked river water samples (Corumbataí and Piracicaba river) with satisfactory uptake values (CDGT-SCG/Csol) between 0.74 and 1.53. The proposed DGT-SCG opens opportunities for using residual biomass as binding phase in the DGT technique, showing low costs in production and complying with “green” technology approaches.
Keywords: Labile species; Macro-DGT; Metal; River water; Spent coffee grounds